Constant-gm constant-slew-rate high-bandwidth low-voltage rail-to-rail CMOS input stage for VLSI cell libraries. - Carrillo, J.M (IEEE Journal of solid state circuits)
This paper introduces a general-purpose low-voltage rail-to-rail input stage suitable for analog and mixed-signal applications. The proposed circuit provides, simultaneously, constant small-signal and large-signal behaviors over the entire input common-mode voltage range, while imposing no appreciable constraint for high-frequency operation. In addition, the accuracy of the circuit does not rely on any strict matching of the devices, unlike most of the traditional approaches based on complementary input pairs, which need to compensate for the difference in mobility between electrons and holes with the transistor aspect ratios. Also, the technique is compatible with deep submicrometer CMOS devices, where the familiar voltage-to-current square law in saturation is not completely satisfied. Based on the proposed input stage, a transconductor with rail-to-rail input common-mode range and an input/output rail-to-rail operational amplifier were developed. Both cells were designed to operate with a 3-V single supply and fabricated in standard 0.8-μm CMOS technology. Experimental results are provided.